2000
DOI: 10.1128/mcb.20.6.2004-2013.2000
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of the SWI-SNF Chromatin Remodeling Complex as a Mechanism of Gene Activation by the Glucocorticoid Receptor τ1 Activation Domain

Abstract: The SWI-SNF complex has been shown to alter nucleosome conformation in an ATP-dependent manner, leading to increased accessibility of nucleosomal DNA to transcription factors. In this study, we show that the SWI-SNF complex can potentiate the activity of the glucocorticoid receptor (GR) through the N-terminal transactivation domain, 1, in both yeast and mammalian cells. GR-1 can directly interact with purified SWI-SNF complex, and mutations in 1 that affect the transactivation activity in vivo also directly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 51 publications
8
84
0
1
Order By: Relevance
“…On MMTV LTR DNA reconstituted into polynucleosome arrays with Drosophila embryo extracts, puri®ed GR required ATP and HeLa nuclear extract to induce chromatin remodeling (Fletcher et al, 2000). Yeast Swi/Snf stimulated transcription via the N-terminal transactivation domain of the GR, tl, from assembled chromatin templates (Wallberg et al, 2000). In the same report, BRM potentiated tl-dependent activation of a transiently introduced glucocorticoid-responsive promoter in human cervical carcinoma cells.…”
Section: Gr and Chromatin-remodeling Complexesmentioning
confidence: 52%
“…On MMTV LTR DNA reconstituted into polynucleosome arrays with Drosophila embryo extracts, puri®ed GR required ATP and HeLa nuclear extract to induce chromatin remodeling (Fletcher et al, 2000). Yeast Swi/Snf stimulated transcription via the N-terminal transactivation domain of the GR, tl, from assembled chromatin templates (Wallberg et al, 2000). In the same report, BRM potentiated tl-dependent activation of a transiently introduced glucocorticoid-responsive promoter in human cervical carcinoma cells.…”
Section: Gr and Chromatin-remodeling Complexesmentioning
confidence: 52%
“…These results suggest that SRG3 may modulate the sensitivity to GC-induced apoptosis by directly regulating the transcriptional activity of GR. In addition, it has been also shown that GR physically interacts with the SWI/SNF complex, and trans-activation of GR requires Brg1/BAF chromatin remodeling complex (29,50). Whether SRG3 affects the transcriptional activity of GR independently or as a component of SWI/SNF complex remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…7A). This model may also explain mechanisms of potential interference with p300 activity by SYT-SSX (23). Second, SSX1C recruits the SNF/SWI complexes to aberrant target sites by interacting with modified chromatin (e.g.…”
Section: Possible Molecular Mechanisms Of Malignant Transformation Bymentioning
confidence: 99%